Optimizing nanoparticle selection for enhanced oil recovery in carbonate rock using hybrid low salinity water flooding - Sunlee Han; Youngsoo Lee (Journal of Petroleum Exploration and Production Technology)
Abstract This study explores the potential of SiO2 and Al2O3 nanoparticles (NPs) to enhance oil recovery in carbonate reservoirs through a novel hybrid low salinity water flooding (LSWF) approach. By evaluating four injection fluids—deionized (DI) water/SiO2, DI/Al2O3, low salinity water (LSW)/SiO2, and LSW/Al2O3—this research systematically examines their effects on rock surface wettability and interfacial tension. The findings reveal a key finding: the LSW/NP flooding process effectively balances NP-induced plugging and rock dissolution, thereby maintaining the pore structure integrity of carbonate rocks. SiO2 NPs demonstrated a unique ability to shift rock wettability from oil-wet to intermediate-wet conditions, while Al2O3 NPs exhibited superior interfacial activity, significantly reducing interfacial tension. Notably, hydrophobic Al2O3 NPs achieved the most substantial reduction in capillary pressure, facilitating an earlier breakthrough and enhanced oil displacement efficiency. Among all injection fluids, LSW/Al2O3 emerged as the optimal choice, delivering faster and more efficient oil recovery compared to DI/NP systems. This study is pivotal in demonstrating the combined effects of LSW and tailored NP properties, offering a effective approach for enhanced oil recovery (EOR) in carbonate reservoirs. The findings underscore the importance of selecting appropriate NPs to optimize hybrid LSWF processes and provide practical guidance for the design of next-generation EOR technologies.